Welded microstructure and orientation variation of duplex Ti alloy through electrodynamic vibration - Chia-Heng Liu; Chen-Kuan Kuo; Shing-Hoa Wang; Yo-Lun Yang; Horng-Yi Chang; Po-Kai Chiu (Journal of Materials Research and Technology, 2022)
Duplex Ti alloys are widely used in the petrochemical industry as well as in the biomedical, aeronautics and astronautics engineering fields. A duplex Ti alloy weldment is uniform and has superior properties in terms of welded microstructure evolution, grain refinement, and microhardness distribution. These properties are believed to be obtainable through tungsten inert gas arc welding with a combination of electrodynamic vibration and active flux. This combination changes the welded metal to phase transformation products, leading to the reappearance of numerous low-angle grain boundaries (≤5°). Vibration is presumed to disturb the heat transfer and temperature gradient in a liquid melt welding pool, enhancing the nucleation and cooling rates. The final result is the rapid formation of many basket weave-like fine parallel elongated α′ sheaths containing the β-phase in the solidified welded metal.